ERNESTO ELIGIO TABÍO PALMA AND PERUVIAN ARCHAEOLOGY - Yataco Capcha, Juan (2013)
On February 5, 1984, Ernesto Tabío Palma died in Cuba at seventy-two years old, ending six decades of continuous scientific productivity. Tabío left no autobiography, much less an assessment of the significant events in his life in Perú from 1953 to 1960. However, his career deserves an honorable place in the history of the Peruvian archaeology. He played a major role in Perú, compiling archaeological collections from sites along the entire Peruvian coast. His contributions to the field included investigations in Playa Grande, Ancón, Puruchuco sites, as well as a long list of publications in Cuba. Tabío Palma also produced one of the great doctoral theses of Peruvian archaeology developed via Marxist theory (1969b) in which he applied this methodology to archaeological material from the Casma, Huarmey, and Fortaleza valleys on the Central Coast of Perú.